Efficiency analysis of the Chilean sawmill industry - Mejías Caballero, Wilson Alexander; Poblete, Pamela; Gysling, Janina; Ganguly, Indroneil; Sepúlveda Oehninger, Daniel (Maderas. Ciencia y Tecnología, 2025)
Chile plays a significant role in global sawn wood production, ranking 14th in total roundwood and 10th in coniferous sawn wood production in 2022, contributing significantly to the demand for wood products. In the same year, the country exported wood products worth a remarkable US 6.682 million of, underscoring its importance in the global wood industry. Despite its prominence, the sector has faced significant including mega forest fires and the COVID-19 pandemic, which have adversely affected its performance. One notable issue is the decline in the number of active sawmill units, with only 61 currently producing sawn wood with structural characteristics. The highlights the pressing need to quantify and optimize efficiency within the industry. To address this, Stochastic Frontier Analysis a valuable mathematical framework for evaluating industry efficiency, was employed. Using a dataset compiled by the Chilean Forestry Institute and applying the Stochastic Frontier Analysis methodology, this research assessed the average efficiency of the Chilean sawmill sector. The analysis, based on two different models, consistently revealed a decline in average efficiency during the pandemic. Furthermore, it identified a longitudinal gradient in the efficiency of sawn wood production, with technical inefficiency decreasing towards the southern regions of the country. However, the study did not find direct evidence of a correlation between productivity and the production scale of sawmills. Instead, cost factors, including raw materials, labor, and supplementary expenses, emerged as critical areas requiring careful attention to improve the overall efficiency of the industry.